389 PARATHYROID CARCINOMA: A CASE REPORT. Issue 1 (1st January 2007) - Sahasranam, P.; Tran, M. T.; Friedman, T. C.
Abstract : A 53-year-old man with no past medical history was admitted with complaints of hematuria and flank and abdominal pain, for a duration of 1 week. He also complained of bone pain, fatigue, nausea, weight loss, and an enlarging new neck mass 1 month prior to the presentation. He admitted to a history of smoking in the past and no significant family history. On admission, his vital signs were stable. Initial laboratory results showed serum calcium 17.3 mg/dL (normal 8.5-10.5 mg/dL), serum albumin 2.9 g/dL (normal 3.0-5.0 g/dL), blood urea nitrogen 48 mg/dL (normal 7-18 mg/dL), serum creatinine 3.4 mg/dL (normal 0.5-1.2 mg/dL), serum phosphorus 4.3 mg/dL (normal 2.5-4.6 mg/dL), serum magnesium 2.2 mg/dL (normal 1.8-2.8 mg/dL), urine analysis positive for moderate amount of blood, alkaline phosphatase 121 IU/L (normal 44-147 IU/L), hemoglobin 8.4 g/dL (normal 13-18 g/dL), hematocrit 24.5 (normal 37-49%), and intact PTH 1, 491 pg/mL (normal 10-65 pg/dL). A sestamibi scan done subsequently was negative. A neck sonogram showed a complicated left neck mass measuring 3.4 cm × 2.2 cm × 1.7 cm with a thick septum and a cystic component. A renal sonogram showed bilateral renal cysts and two stones each measuring 10 mm on the left kidney. The chest radiograph was normal. He was hydrated for a week with improvement in his laboratory tests showing serum calcium decreased to 9.3 mg/dL and a serum creatinine of 1.8 mg/dL. He underwent a total thyroidectomy and parathyroidectomy. The pathology showed bilateral parathyroid carcinoma infiltrating the capsule, invading the capsule, and adhering to the thyroid, with evidence of lymphovascular invasion. The immunohistochemical staining was negative for p53 and Ki67. After surgery, his symptoms significantly improved and laboratory tests done 2 weeks later showed the following: calcium 7.8 mg/dL, intact PTH 7 pg/mL, TSH 15 mIU/L, and FT4 0.6 μg/dL. A DXA scan showed osteoporosis. Postoperative management included treatment of hypothyroidism, hypoparathyroidism, osteoporosis, and chronic renal insufficiency. Two years later, he continues to be asymptomatic on medications with normal biochemical parameters. A high degree of suspicion is required to diagnose parathyroid carcinoma. A better knowledge and understanding of this condition would aid in early diagnosis and possibly increase in survival rate.